Distribuição de sequências centroméricas de Solanum nos genomas A, C e D de espécies alopoliploides - Oliveira, Gleicy Kelly de (2017)
In the genus Solanum, the genomes A, P, B, C, D and E are identified based on studies of compatibility and chromosomal homology in interspecific hybrids. Characterization of centromeric repetitive sequences in species with some of these genomes have been shown that the dynamic of centromeric DNA is very distinct in Solanum. The centromere is a chromosomal locus usually made up of large sets of satellite DNA and/or transposable elements, responsible for the accurate segregation of the genetic material during cell division. Centromeric satellite repeats were identified in the species Solanum tuberosum, Solanum verrucosum and Solanum chomatophilum (carriers of the A, A and P genomes, respectively) and the distribution of these sequences in wild diploid potato species with genomes A, P, B, E was described. However, these repeats have not yet been evaluated in genomes C and D, present only in polyploid species, in association with genome A. The aim of this study was to verify the distribution pattern and the organization of centromeric sequences in the genomes A and P of Solanum, in the chromosomes of alopoliploid species (carriers of the AC and AD genomes) using the FISH technique. The centromeric sequences used as probes were obtained from S. tuberosum (St49 and St18), S. verrucosum (Sv54, Sv123, Sv161.5) and S. chomatophilum (Sc83, Sc111, Sc9 / 108). The rDNA sequence 45S was used as a positive control in experiments with centromeric probes. In the AC genome, the St18 and St49 probes were absent. In the AD genome the St18 repeat was also absent and the St49 sequence was present in the centromeric region of multiple AD chromosomes. The Sv54 sequence generated 4 centric signals in the AD genome and was absent in the AC genome. Regarding the AD genome, Sv 161.5 revealed four centromeric signals on two chromosome pairs, while in the AC genome, Sv 161.5 showed two centromeric signals in one chromosomal pair. Sv 123, revealed in both AC and AD genomes two signals in the centromere in one chromosomal pair. In the AC genome, the Sc83 probe generated scattered, non-centromeric signals along the chromosomes. In the AD genome, this same probe revealed two centromeric signals in one chromosome pair of the complement. In the AD genome, Sc92/108 revealed four intense signals in the centromeric regions of two pairs of chromosomes, whereas in the AC genome there was no signal. In AC, the Sc 111 probe showed dispersed signals, with higher intensity in the centromere. In the AD genome, the Sc111 repeat showed scattered signals in all chromosomes, as well as seven signals with higher intensity in centromeric and noncentromeric regions, four of them co-localized with Sc92/108. In general, the identified sequences in alopoliploids belong mostly to chromosomes of genome A , with a patter similar either to the genome A of S. tuberosum or S. verrucosum. None of the analyzed sequences is candidate to belong to genome C, whereas for genome D the sequence Sc83 can belong to this genome, with pattern similar to the genome P.